Prevention of diarrhea and acute lower respiratory infection by zinc supplementation in developing country children: pooled analysis of randomized control trials - Black, R.; Bhutta, Zulfiqar A.; Brown, Kenneth H.; Gardner, J.; Gore, S.; Kidayat, A.; Khatun, F.; Martorell, Reynaldo; Ninh, N.; Penny, M.; Rosado, J.; Roy, S.; et al. (Elsevier, 1999)
This study assessed the effects of zinc supplementation in the prevention of diarrhea and pneumonia with the use of a pooled analysis of randomized controlled trials in children in developing countries....Conclusions: Zinc supplementation in children in developing countries is associated with substantial reductions in the rates of diarrhea and pneumonia, the 2 leading causes of death in these settings.